High‐Flow Nasal Cannula Therapy for Exertional Dyspnea in Patients with Cancer: A Pilot Randomized Clinical Trial. (14th December 2020) - Hui, David; Mahler, Donald A.; Larsson, Liliana; Wu, Jimin; Thomas, Saji; Harrison, Carol A.; Hess, Kenneth; Lopez‐Mattei, Juan; Thompson, Kara; Gomez, Daniel; Jeter, Melenda; Lin, Steven; et al.
Abstract: Background: Exertional dyspnea is common in patients with cancer and limits their function. The impact of high‐flow nasal cannula on exertional dyspnea in nonhypoxemic patients is unclear. In this double‐blind, parallel‐group, randomized trial, we assessed the effect of flow rate (high vs. low) and gas (oxygen vs. air) on exertional dyspnea in nonhypoxemic patients with cancer. Patients and Methods: Patients with cancer with oxygen saturation >90% at rest and exertion completed incremental and constant work (80% maximal) cycle ergometry while breathing low‐flow air at 2 L/minute. They were then randomized to receive high‐flow oxygen, high‐flow air, low‐flow oxygen, or low‐flow air while performing symptom‐limited endurance cycle ergometry at 80% maximal. The primary outcome was modified 0–10 Borg dyspnea intensity scale at isotime. Secondary outcomes included dyspnea unpleasantness, exercise time, and adverse events. Results: Seventy‐four patients were enrolled, and 44 completed the study (mean age 63; 41% female). Compared with low‐flow air at baseline, dyspnea intensity was significantly lower at isotime with high‐flow oxygen (mean change, −1.1; 95% confidence interval [CI], −2.1, −0.12) and low‐flow oxygen (−1.83; 95% CI, −2.7, −0.9), but not high‐flow air (−0.2; 95% CI, −0.97, 0.6) or low‐flow air (−0.5; 95% CI, −1.3, 0.4). Compared with low‐flow air, high‐flow oxygen also resulted in significantly longer exercise time (difference + 2.5 minutes, p = .009), but not low‐flow oxygen (+0.39 minutes, p = .65) or high‐flow air (+0.63 minutes, p = .48). The interventions were well tolerated without significant adverse effects. Conclusion: Our preliminary findings support that high‐flow oxygen improved both exertional dyspnea and exercise duration in nonhypoxemic patients with cancer. (ClinicalTrials.gov ID: NCT02357134). Implications for Practice: In this four‐arm, double‐blind, randomized clinical trial examining the role of high‐flow nasal cannula on exertional dyspnea in patients with cancer without hypoxemia, high‐flow oxygen, but not high‐flow air, resulted in significantly lower dyspnea scores and longer exercise time. High‐flow oxygen delivered by high‐flow nasal cannula devices may improve clinically relevant outcomes even in patients without hypoxemia. Abstract : A better understanding of the effect of high flow rate and gas type on exertional dyspnea may facilitate the use of high‐flow oxygen as an intervention to improve dyspnea, function, and quality of life. This clinical trial assessed the effect of flow rate (high vs. low) and gas (oxygen vs. air) on exertional dyspnea in nonhypoxemic patients with cancer.